2018
DOI: 10.1038/s41598-018-34718-8
|View full text |Cite
|
Sign up to set email alerts
|

Hydrostatic pressure-generated reactive oxygen species induce osteoarthritic conditions in cartilage pellet cultures

Abstract: Osteoarthritis (OA) is one of the most common causes of disability and represents a major socio-economic burden. Despite intensive research, the molecular mechanisms responsible for the initiation and progression of OA remain inconclusive. In recent years experimental findings revealed elevated levels of reactive oxygen species (ROS) as a major factor contributing to the onset and progression of OA. Hence, we designed a hydrostatic pressure bioreactor system that is capable of stimulating cartilage cell cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 68 publications
1
25
0
Order By: Relevance
“…Among them, Young et al [25] observed an increased production of ROS, as hydrogen peroxide and hydroxyl radicals, after applying 24 h of static compression ranged from 40 to 120 psi at porcine chondrocytes. A similar increase of ROS species was observed by Rieder et al [13] upon the application, at human adipose tissue derived stromal cells, of 4 h of intermittent stimulation of 0 and 4 bars for 5 consecutive days/week for 21 days. The results of our study partially sustain these data even though the experimental protocols are not comparable.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Among them, Young et al [25] observed an increased production of ROS, as hydrogen peroxide and hydroxyl radicals, after applying 24 h of static compression ranged from 40 to 120 psi at porcine chondrocytes. A similar increase of ROS species was observed by Rieder et al [13] upon the application, at human adipose tissue derived stromal cells, of 4 h of intermittent stimulation of 0 and 4 bars for 5 consecutive days/week for 21 days. The results of our study partially sustain these data even though the experimental protocols are not comparable.…”
Section: Discussionsupporting
confidence: 84%
“…In OA, the redox balance has lost and the excessive ROS formation participates to alter gene expression and promotes genomic instability, exacerbating cartilage destruction, synovitis, and apoptosis [21][22][23]. It has been reported an association between mechanical stress and the regulation of oxidant/antioxidant system, even if, data from the literature are poor [13,[24][25][26]. Among them, Young et al [25] observed an increased production of ROS, as hydrogen peroxide and hydroxyl radicals, after applying 24 h of static compression ranged from 40 to 120 psi at porcine chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HP appears to affect hypertrophic genes, increasing Col I, Col X and MMP13 (Ogawa et al, 2009 , 2015 ; Li et al, 2016 ). Conversely, other studies revealed decreasing levels of Col I and Col X under IHP (Vinardell et al, 2012 ; Saha et al, 2017 ; Rieder et al, 2018 ). Freeman et al ( 2017 ) demonstrated that HP without any external growth factors resulted in enhanced chondrogenesis along with reduction in hypertrophic markers.…”
Section: Mechanical Cues Affecting Stem Cell Differentiationmentioning
confidence: 84%